2018
DOI: 10.1007/s12325-018-0754-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a Single Dose of Azilsartan in Pediatric Patients: A Phase 3, Open-Label, Multicenter Study

Abstract: IntroductionAzilsartan is an angiotensin II receptor blocker indicated for the treatment of patients with hypertension. The efficacy and safety of azilsartan are established in adults, but have not been evaluated in pediatric patients, nor has its pharmacokinetic profile been determined in pediatric patients.MethodsIn this phase 3, open-label, multicenter study, we investigated the pharmacokinetics and safety of single doses of azilsartan in six Japanese patients with hypertension, aged 9–14 years. The dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Previous clinical trials in the United States and Europe have indicated that the BP-lowering effects of ARBs (candesartan, cilexetil and valsartan) in children are consistent with those in adults [9,10]. A single-dose, phase 3 study evaluating the pharmacokinetics and safety of azilsartan in Japanese children with hypertension reported no unexpected safety issues [11]. The Japanese study also showed that for the same dose, exposure to azilsartan in paediatric patients weighing ≥ 50 kg was comparable to that in healthy adults; however, in children weighing < 50 kg, the exposure was approximately twice as high [11].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous clinical trials in the United States and Europe have indicated that the BP-lowering effects of ARBs (candesartan, cilexetil and valsartan) in children are consistent with those in adults [9,10]. A single-dose, phase 3 study evaluating the pharmacokinetics and safety of azilsartan in Japanese children with hypertension reported no unexpected safety issues [11]. The Japanese study also showed that for the same dose, exposure to azilsartan in paediatric patients weighing ≥ 50 kg was comparable to that in healthy adults; however, in children weighing < 50 kg, the exposure was approximately twice as high [11].…”
Section: Introductionmentioning
confidence: 93%
“…A single-dose, phase 3 study evaluating the pharmacokinetics and safety of azilsartan in Japanese children with hypertension reported no unexpected safety issues [11]. The Japanese study also showed that for the same dose, exposure to azilsartan in paediatric patients weighing ≥ 50 kg was comparable to that in healthy adults; however, in children weighing < 50 kg, the exposure was approximately twice as high [11]. Herein, we evaluate the long-term safety and efficacy of azilsartan in young patients with hypertension in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…AZL is highly bound to human plasma proteins (>99%), mainly serum albumin. The volume of distribution of AZL is approximately 16 L. The pharmacokinetic characteristics of AZL are practically identical to those of its prodrug azilsartan medoxomil …”
mentioning
confidence: 89%
“…After oral administration, plasma concentrations of AZL peak within 1.8‐2.4 hours, and the elimination half‐life (t ½ ) is approximately 13 hours . AZL is eliminated through both renal clearance and hepatic metabolism . Its renal clearance is 0.138 L/h, and its apparent oral clearance is 1.5 L/h.…”
mentioning
confidence: 99%